HUBUNGAN LAMANYA TERAPI HEMODIALISA DENGAN PERUBAHAN MENSTRUASI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD WALED KABUPATEN CIREBON - Noni Ardiyani; Endah Sari Purbaningsih; Ika Nurfajriani (Jurnal Kesehatan Mahardika, 2019)
The number of patiens undergoing hemodialysis therapy at Waled General Hospital Cirebon in 2018 amounted to 77 patients. Patients with cronic kidney disease who underwent hemodialysis at Waled General Hospital Cirebon experience Menstrual Changes. The purpose of this study was to determine Relationship Long Time Of Hemodialyisis Therapy With Menstrual Changes Of Cronic Kidney Disease Patient who Undergoing Hemodialysis at Waled General Hospital Cirebon. This research used descriptive correlational with cross sectional approach. The population of the study was55 female patients undergoing hemodialysis therapy from December 2019 to February 2019. A total of 48 respondens participated as the sample by using Purposive Sampling tecniques. The documentation sheet and questionnaires were attempted as the instrument of study and data were analyzed by using chi square (x2).The study was held in RSUD Waled Hospital Cirebon. On 2nd – 6th July, 2019. The results of the study obtained r value of 0.707 and< α H0 rejected. It showed there was an relationship long time of hemodialyisis therapy with menstrual changes of cronic kidney disease patient who undergoing hemodialysis at Waled General Hospital Cirebon ( p value = 0.027, α = 0.05 r = 0,707). The long time of hemodialysis therapy affects the menstrual cycle changes can occur due to the presence of hyperprolactinemia so that the changes that occur can be secondary amenorrhea.